Steeped in secrets - Elliott, Lauren (Elliott, Lauren. Crystals & CuriosiTEAS mystery, 2023)
Flat broke and divorced, intuitive gemologist Shay Myers has changed since leaving her artsy hometown of coastal Bray Harbor sixteen years ago. But when she moves back under strange circumstances, old instincts may be the only key to spilling the tea on a deadly mystery. Even with her life in ruins in New Mexico, Shay feels uneasy about settling into the small seaside town where she grew up on California's Monterey Peninsula and taking over an estate bequeathed to her by Bridget Early, a woman she had barely known. Her heightened senses--an empathic gift she's had since childhood--go into overdrive upon touring Crystals & CuriosiTEAS, Bridget's eclectic tea and psychic shop brimming with Irish lore and Celtic symbols. They reach a boiling point when Shay looks up to discover a stranger's body sprawled across the shop's greenhouse roof ... With her new business a crime scene and questions brewing over Bridget's so-called accidental death, Shay fears she's also inherited the attention of a killer. The terrifying realization sets her on an impractical investigation for answers aided by her sister, an elusive pure-white German Shepherd, a strikingly handsome pub owner who speaks in a gentle brogue, and a misunderstood young woman with perceptive talents of her own. As Shay struggles to figure out her true purpose in Bray Harbor and the powerful connection she has with the tea shop, she must trust her judgment above all else to identify a ruthless murderer and save herself from becoming victim number three.